2021
DOI: 10.1007/s11606-021-06888-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an eHealth intervention on older adults’ quality of life and health-related outcomes: a randomized clinical trial

Abstract: Background By 2030, the number of US adults age ≥65 will exceed 70 million. Their quality of life has been declared a national priority by the US government. Objective Assess effects of an eHealth intervention for older adults on quality of life, independence, and related outcomes. Design Multi-site, 2-arm (1:1), non-blinded randomized clinical trial. Recruitment November 2013 to May 2015; data collection through No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 38 publications
2
29
0
8
Order By: Relevance
“…A total of 11 themes and 2 individual observations were identified by the reviewers for a total of 48 occurrences in the literature, whereas 11 themes and 7 observations were noted for a total of 95 observations. In the 33 studies analyzed, 26 (79%) showed an improvement in symptoms of depression [25,26,[28][29][30][31][32][33][35][36][37][40][41][42][43][44][46][47][48][49][50][51][52][54][55][56], while 19 (58%) showed an improvement in anxiety [26][27][28][29][30][31][32][33]36,[38][39][40][44][45][46][53][54][55][56]. Only 11/33 (33%) reported that at least one symptom was not statistically significant when compared with results from the control group, but the improvement was still noted [25]…”
Section: Results Of Interventions Compared With the Control Groupsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 11 themes and 2 individual observations were identified by the reviewers for a total of 48 occurrences in the literature, whereas 11 themes and 7 observations were noted for a total of 95 observations. In the 33 studies analyzed, 26 (79%) showed an improvement in symptoms of depression [25,26,[28][29][30][31][32][33][35][36][37][40][41][42][43][44][46][47][48][49][50][51][52][54][55][56], while 19 (58%) showed an improvement in anxiety [26][27][28][29][30][31][32][33]36,[38][39][40][44][45][46][53][54][55][56]. Only 11/33 (33%) reported that at least one symptom was not statistically significant when compared with results from the control group, but the improvement was still noted [25]…”
Section: Results Of Interventions Compared With the Control Groupsmentioning
confidence: 99%
“…The following observations only occurred once in the literature: decrease in anger [26], decrease in decision conflict [30], decrease in decision regret [30], decreased digestive disturbance [26], decreased pain [26], increased medication adherence [41], and the intervention had no effect on self-efficacy [34]. [25,26,[28][29][30][31][32][33][35][36][37][40][41][42][43][44][46][47][48][49][50][51][52][54][55][56] 19 Reduced anxiety [26][27][28][29][30][31][32][33]36,[38][39][40][44][45][46][53]…”
Section: Results Of Interventions Compared With the Control Groupsmentioning
confidence: 99%
See 3 more Smart Citations